2015
DOI: 10.1186/s40594-015-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

STEM learning through engineering design: fourth-grade students’ investigations in aerospace

Abstract: Background: Internationally, there is a growing concern for developing STEM education to prepare students for a scientifically and technologically advanced society. Despite educational bodies lobbying for an increased focus on STEM, there is limited research on how engineering might be incorporated especially in the elementary school curriculum. A framework of five comprehensive core engineering design processes (problem scoping, idea generation, design and construction, design evaluation, redesign), adapted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 35 publications
3
116
0
17
Order By: Relevance
“…The result showed that the average of animal and plant cell model design is at expressing category which means that their products, projects or performance include evidence of fluency, flexibility, originality, or abstractness that are consistently spontaneous in individual work. This indicates that students were able to perform the design process [28]. In STEM-based learning, students had possessed the potentials to create design and redesign [28].…”
Section: Creativity and Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that the average of animal and plant cell model design is at expressing category which means that their products, projects or performance include evidence of fluency, flexibility, originality, or abstractness that are consistently spontaneous in individual work. This indicates that students were able to perform the design process [28]. In STEM-based learning, students had possessed the potentials to create design and redesign [28].…”
Section: Creativity and Collaborationmentioning
confidence: 99%
“…This indicates that students were able to perform the design process [28]. In STEM-based learning, students had possessed the potentials to create design and redesign [28]. Through the design process, the students were involved in the initial engineering process, in which they could implement their STEM knowledge.…”
Section: Creativity and Collaborationmentioning
confidence: 99%
“…Despite the increasing interest in providing learning experiences that help students make connections across the STEM disciplines, there is limited research on which of the different STEM integration approaches best facilitate these connections and what factors make integration more likely to increase student learning, interest, or achievement in STEM (English and King, 2015;National Research Council, 2014). Additionally, while integration is not a new idea, STEM content has historically been taught in a siloed-manner that can make the recommended approaches of integrating across specific disciplines more challenging (Bybee 2010; National Academy of Engineering and National Research Council 2009;National Research Council 2014,).…”
Section: Stem Integration and Engineering Designmentioning
confidence: 99%
“…Research, even in its infancy, indicates that the inclusion of engineering experiences within the STEM curriculum can develop young students' understanding of the various roles of engineering within the society as well as helping to enhance achievement, motivation, and problem solving by contextualizing mathematics and science content (Brophy et al 2008;English and King 2015;Stohlmann et al 2012). Elementary classrooms, therefore, provide a powerful environment for STEM implementation and learning.…”
Section: Introductionmentioning
confidence: 99%
“…FeTeMM eğitimi denildiğinde maalesef farklı kişiler farklı tanımlar ortaya koymakta ve dolayısıyla farklı yorumlar ortaya çıkmaktadır (English ve King, 2015). "FeTeMM kısaltması, bu alanda çalışanlar için bile muğlak bir kısaltmadır" (Sanders, 2009, s. 20).…”
Section: Fetemm Eğitimi Yaklaşımı Ne Anlama Gelmektedir?unclassified